Do Child Development Accounts Promote Account Holding, Saving, and Asset Accumulation for Children's Future? Evidence from a Statewide Randomized Experiment. (23rd July 2012) - Nam, Yunju; Kim, Youngmi; Clancy, Margaret; Zager, Robert; Sherraden, Michael
Abstract This study examines the impacts of Child Development Accounts (CDAs) on account holding, saving, and asset accumulation for children, using data from the SEED for Oklahoma Kids experiment (SEED OK). SEED OK, a policy test of universal and progressive CDAs, provides a 529 college savings plan account to every infant in the treatment group with automatic account opening and an initial deposit. SEED OK also encourages treatment participants to open their own 529 accounts with an account opening incentive and a savings match. Using a sample of infants randomly selected from birth records (N = 2, 670) and randomly assigned to treatment and control groups, this study runs probit and ordinary least squares (OLS) regressions. Analyses show significant differences between treatment and control groups in all outcome measures in the targeted accounts. Nearly 100 percent of the treatment group accepted the automatically opened state‐owned account. Compared to 1 percent of the control group, 16 percent of the treatment group hold a participant‐owned account. On average, the treatment group has saved significantly larger amounts in participant‐owned accounts, although a difference in savings amount is modest between the two groups (47 vs. 13). A difference in total 529 assets of 1, 040 is estimated between the treatment and control groups. These early findings from SEED OK suggest that CDAs have positive effects on savings and asset accumulation for children's future development. Further research is required to test long‐term cost effectiveness of CDAs.